Lumboscopic-assisted pyeloplasty: A single-port, retroperitoneoscopic approach for children with pelvi-ureteric junction obstruction - Minu Bajpai; Kashish Khanna; Vikram Khanna; Prabudh Goel; Dalim Kumar Baidya (Wolters Kluwer Medknow Publications, 2020)
Introduction: Pelvi-ureteric junction obstruction (PUJO) is one of the most common conditions presenting to a pediatric urologist. As laparoscopic or robotic-assisted pyeloplasty, either transperitoneal or retroperitoneal, involves intracorporeal suturing skills and has a long learning curve, they have not gained popularity among beginners in laparoscopy. Objective: We conducted a study to assess the results of a single-port, retroperitoneoscopic approach to renal access, i.e. lumboscopic-assisted pyeloplasty (LAP), by single surgeon at our institute. Materials and Methods: A retrospective review of all children who underwent LAP from July 2013 to March 2018 was conducted. Patients who presented with PUJO and required surgical treatment were included. A single-port lumboscopy using coaxial telescope was performed in prone position in all patients. The renal pelvis was dissected and retrieved through the port site followed by extracorporeal hand-sewn pyeloplasty over a double-J stent or a nephrostent. The operative time, postoperative pain, surgical complications, duration of hospital stay, follow-up, and cosmesis at 6 months postsurgery were evaluated. Results: A total of 96 children were included (72 males and 24 females), with the age at operation ranging from 3 months to 10 years (mean = 4.9 years). All patients had an uneventful postoperative recovery. Two patients had a superficial wound infection, and one patient was converted to open approach due to excessive bleeding. The average operating time was 80 ± 22.5 min, the median duration of hospital stay was 3 days, and the average scar length at 3 months was 15.6 ± 0.4 mm. Follow-up renogram (diethylenetriamine pentaacetic acid) showed satisfactory postpyeloplasty drainage pattern in 93 children while three showed obstructive drainage curves. Conclusion: LAP can be performed safely with minimal retroperitoneal dissection, excellent cosmetic results, and minimal postoperative pain in children with PUJO. It has a shorter learning curve as compared to laparoscopic pyeloplasty as it involves time tested extracorporeal hand-sewn anastomosis.